2009
DOI: 10.1016/s1081-1206(10)60139-1
|View full text |Cite
|
Sign up to set email alerts
|

Household airborne Penicillium associated with peak expiratory flow variability in asthmatic children

Abstract: Background-Exposure to airborne fungi has been associated with increased airway hyperreactivity and asthma prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 32 publications
(26 reference statements)
2
32
0
Order By: Relevance
“…A prospective study by Bundy et al found indoor Penicillium to be associated with increased peak expiratory flow variability greater than 18.5% (OR 2.4; CI 1.2-4.8). 35 The authors of the review concluded that there was limited evidence of an association between indoor culturable Penicillium exposure and exacerbations in asthmatic children.…”
Section: Indoor Fungal Exposure and Current Asthmamentioning
confidence: 99%
“…A prospective study by Bundy et al found indoor Penicillium to be associated with increased peak expiratory flow variability greater than 18.5% (OR 2.4; CI 1.2-4.8). 35 The authors of the review concluded that there was limited evidence of an association between indoor culturable Penicillium exposure and exacerbations in asthmatic children.…”
Section: Indoor Fungal Exposure and Current Asthmamentioning
confidence: 99%
“…While Penicillium is frequently isolated both in indoor and outdoor environments, 13,15 many studies have focused on the significance of Penicillium as an indoor mold allergen. 11,73,74 Indoor environmental factors, including inadequate heating and ventilation, the presence of pets, water leaks, and low sun exposure, are known to increase the concentrations of airborne Penicillium. 14 Results for Alternaria and Cladosporium spp.…”
Section: Cladosporiummentioning
confidence: 99%
“…(Salo et al, 2006), Penicillium spp. (Bundy et al, 2009), Cladosporium spp. (Garrett et al, 1998) are also involved in respiratory disorders.…”
Section: Introductionmentioning
confidence: 99%